The effectiveness of using Quizizz in improving students’ grammar accuracy - Mohammad Fatoni; Agus Wardhono; Kang Min-ho; Ming Chen Liu (Journal of Research in English Language Teaching and Linguistics, 2025)
This study investigates the effectiveness of using Quizizz, a gamified digital platform, in enhancing students’ grammar accuracy in English Language Teaching (ELT). As grammar proficiency remains fundamental to effective communication, engaging and interactive tools are essential to motivate learners and improve their linguistic skills. The current research highlights the positive impacts of gamification and digital platforms like Quizizz on student engagement, motivation, and grammar retention. However, limited attention has been paid to learners’ subjective experiences and perceptions of using such platforms specifically for grammar learning, leaving a gap in understanding how these tools support meaningful grammar acquisition in authentic classroom contexts. The primary aim of this study is to explore students’ experiences and perceptions of using Quizizz to improve their grammar accuracy. Employing a phenomenological research design, data were collected through semi-structured interviews with nineteen university students who utilized Quizizz in their grammar exercises. Additional data were gathered via classroom observations and researcher field notes to triangulate findings. Thematic analysis was employed to interpret the qualitative data, identifying key themes related to engagement, perceived effectiveness, challenges, and motivational factors. The findings reveal that students generally found Quizizz to be engaging and motivating, citing its game-like interface, immediate feedback, and competitive elements as factors that increased focus and reduced anxiety. Participants perceived the platform as beneficial for repetitive practice and self-correction, which contributed to improved confidence in grammar use. Nevertheless, some participants expressed concerns about limited feedback depth and dependency on internet connectivity. These insights suggest that while Quizizz supports active learning and motivation, it should be integrated with explicit instruction and deeper grammatical explanations.